New Views on Old Topics? The Independence of Mexico in its Bicentennial (Historiographic Notes) - Escrig, Josep; Frasquet, Ivana (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2024)
Mexican historiography has revised the traditional readings of the so-called «consummation of Independence» on the occasion of the bicentenary. We refer to the transition from the former viceroyalty to a province of the Spanish constitutional monarchy and, later, to an independent constitutional empire (1820-1823). The commemorative cycle had 2021 as its central date. The moment was marked by the lasting effects of the pandemic, the political context and a range of academic events and publications. In this paper we propose to identify some of the main contributions to a fuller and more complex understanding of the period. In doing so, we outline the issues that have attracted the most attention and interest, the approach that has been adopted to address them, and what has tended to be omitted or silenced. Certainly, reference to the implications of the use of the term «consummation» as part of the founding myths is unavoidable.
Keywords: Consummation of Independence; Mexico; bicentenary; First Empire; historiography